A comparative study of structural and electrical properties in lead-free BCZT ceramics: Influence of the synthesis method. (15th August 2018) - Coondoo, Indrani; Panwar, Neeraj; Alikin, Denis; Bdikin, Igor; Islam, Saikh S.; Turygin, Anton; Shur, Vladimir Ya; Kholkin, Andrei L.
Abstract: In the present work, various grain size phenomena were studied in promising lead-free piezoelectric ceramics (Ba0.85 Ca0.15 ) (Zr0.10 Ti0.90 )O3 fabricated via chemical and conventional oxide methods. Phase composition was ascertained by the Rietveld refinement. Average grain size estimated from the microstructure was ∼1.5 μm in the sol-gel derived ceramic (SG-BCZT) which was much smaller than that obtained in coarse grained (∼27 μm) sample prepared by solid state method (SS-BCZT). Systematic investigation of various functional properties viz . dielectric, ferroelectric, piezoelectric and impedance emphasized the profound influence of grain size effects. The increase in grain boundary volume fraction enhanced diffuseness while lowered the dielectric peak in SG-BCZT. Similarly, increase in elastic stiffness and progressive hindrance to domain wall movements, resulted in a decrease of the remnant polarization and the associated piezoelectric charge coefficient values in small-grained SG-BCZT sample. Accordingly, higher Young's modulus value of 158.3 GPa was observed in SG-BCZT as compared to 117.9 GPa in SS-BCZT. Local-area piezoresponse force microscopy (PFM) images revealed lamellar domains with periodicity 250 ± 90 nm in SS-BCZT while small sized fractal-like irregular domains with an estimated domain width of 150 ± 60 nm were registered in SG-BCZT. Complex impedance spectroscopy results along with grain boundary conductivity were also guided by grain size effect. The mechanisms of grain size driven effects and their impact on the functional properties were discussed. Graphical abstract: Image 1